The Determinants of Human Wellbeing in Professional Activities; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 19 : Lifelong Wellbeing in the World (WELLSO 2016) - Konyukhova T. V. Tatiana Vasilievna; Konyukhova E. Ekaterina; Kashpur V. Valeriya; Lokotosh Ju. Julia (2017, 2017)
Title screen